2007
DOI: 10.1016/j.pepi.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of CaIrO3 determined by X-ray powder diffraction

Abstract: The thermal expansion of CaIrO 3 , the archetype phase of the "post-perovskite" polymorph of MgSiO 3 , has been determined by X-ray powder diffraction from 113 K to 1173 K. For temperatures above 298 K, the volumetric coefficient of thermal expansion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Restricting the perturbation up to second order as used by Vocadlo et al [32] and Lindsay-Scott et al [33] Eq. (6) turns into be:…”
Section: Dft (Crystal09) Calculated Metric Parametersmentioning
confidence: 99%
“…Restricting the perturbation up to second order as used by Vocadlo et al [32] and Lindsay-Scott et al [33] Eq. (6) turns into be:…”
Section: Dft (Crystal09) Calculated Metric Parametersmentioning
confidence: 99%
“…Early room-temperature deformation experiments have developed textures in MgSiO 3 and MgGeO 3 post-perovskite consistent with slip on (100) or (110) glide planes (Merkel et al 2006. The structure type material, CaIrO 3 , crystallizes in the post-perovskite structure at atmospheric pressure and has been extensively studied as a structural (Martin et al 2007;Boffa Ballaran et al 2007;Lindsay-Scott et al 2007) and mechanical (Yamazaki et al 2006;Niwa et al 2007;Walte et al 2007Walte et al , 2009Miyagi et al 2008;Hunt et al 2009;Miyajima et al 2010) analog to MgSiO 3 . Deformation experiments performed at pressures of a few gigapascals and ~1273-1673 K in deformation-DIA apparatus produced textures consistent with slip on the [100] (010) glide system (Yamazaki et al 2006;Walte et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They recovered samples that showed textures similar to those of the diamond-anvil cell experiments immediately after transformation and these textures evolved into the [100](010) texture typical of CaIrO 3 with further deformation. However, it is not clear that CaIrO 3 is a good analog for MgSiO 3 since it has very different chemical bonding with highly distorted IrO 6 octahedra (Ohgushi et al 2008) and a much larger anisotropy in its axial incompressibilities (Martin et al 2007;Boffa Ballaran et al 2007) and thermal expansivities (Lindsay-Scott et al 2007). Ab initio simulations, however, of generalized stacking fault energies (Metsue et al 2009) suggested that CaIrO 3 is, in fact, a better analog for lower-mantle post-perovskite than is MgGeO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Analogues studied to date include CaIrO 3 (Boffa Ballaran et al, 2007;Lindsay-Scott et al, 2007;Martin et al, 2007Martin et al, , 2007aMartin, 2008;Sugahara et al, 2008;Hirai et al, 2009) and CaPtO 3 (Inaguma et al, 2008;Ohgushi et al, 2008). CaIrO 3 may be synthesised at atmospheric pressure (see e.g.…”
Section: Introductionmentioning
confidence: 99%